Peculiarities of kinematics of rock mass shear during development of subseismic-scale faults - A. V. Merzlikin; L. N. Zakharova (Записки Горного института, 2018)
The article describes the mechanism of formation and development of subseismic-scale faults in sedimentary rock mass based on results of physical and mathematical simulation. Physical modelling of layered rock massif was carried out by using sand-gypsum mixture. The results of physical modeling made it possible to visually evaluate the process of formation and development of subseismic-scale faults, to establish the orientation and amplitude of the modeled faults. It was established that faults with higher amplitude had filler material formed because of friction of fault edges/walls. The volume of modelled formation after formation of faults depending on fault amplitudes changed from 2-3 to 10 %. To gain information on stress deformed condition of rock massif and identification of key peculiarities of fault propagation dynamics we used the mathematical modeling based on particle-flow algorithm. The results of mathematical modeling determined that during formation of low amplitude faults the shear field has several rock clusters. Due to interaction of clusters, which have coordinated movement and promote massif loosening, the rock mass accumulates voids, which are the prerequisite for formation of subseismic-scale faults. The gained results enable to specify the complex mechanism of irreversible shears and deformations of rock mass during formation and development of subseismic-scale faults. It contributes to the improvement of the methodology for predicting the SSF parameters, which is of practical importance in terms of reducing mining risks.